Sex Differences in Characteristics, Treatments, and In-hospital Outcomes of Patients Undergoing Coronary Angiography or Intervention - Chen, Shi-Qun; Liu, Jin; Zhou, Yang; Huang, Zhi-Dong; Xie, Yun; Huang, Hao-Zhang; Yan, Xiao-Ming; Xie, Yong-Yi; Hao, Peng-Fei; Liang, Yan; Dong, Shao-Hong; Huang, Xiao-Yu; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Whether women have a higher risk of adverse events compared with men following coronary angiography (CAG) and percutaneous coronary intervention (PCI) remains controversial. We aimed to investigate the sex differences in characteristics, treatments and outcomes among patients undergoing CAG and PCI in a large Chinese cohort. Methods We analyzed patients undergoing CAG and/or PCI in this multi-center registry cohort study Cardiorenal ImprovemeNt II (CIN-II) in 5 Chinese tertiary hospitals from 2007 to 2020. Clinical characteristics, treatment (discharge medication and PCI) and in-hospital outcomes (mortality and major bleeding) were compared between women and men. Results Totally 141,459 patients underwent CAG (44,362 [31.4%] women), of which 69,345 patients underwent PCI (15,376 [22.2%] women). Women were older (64.4 vs. 60.8 years), had more chronic comorbidities and lower PCI rate for stable coronary artery disease (CAD) than men (52.8% vs. 64.2%). Women received less CAG and PCI procedures. Among women undergoing PCI they received similar discharge medication treatment. In addition, women undergoing PCI had mildly lower rate of major bleeding (0.2% vs. 0.3%, P=0.033) but higher in-hospital mortality (1.2% vs. 0.8%, P<0.001). After adjustment, women had a higher risk in the major bleeding (adjusted odds ratio, 2.04 [95% CI: 1.07 to 3.62]), and the in-hospital mortality (adjusted odds ratio, 1.87 [95% CI: 1.36 to 2.56]). Conclusion Among our Chinese cohort, women are older with more chronic comorbidities, receiving less PCI procedure and similar discharge medication treatment. Women have nearly 90% higher risk of in-hospital mortality and over 1-fold increased risk of major bleeding after PCI compared with men.